Johann Christian Rosenmüller (1771-1820): A Historical Perspective on the Man behind the Fossa - Amene, Chiazo; Cosetti, Maura; Ambekar, Sudheer; Guthikonda, Bharat; Nanda, Anil (Journal of Neurological Surgery Part B: Skull Base, 2013)
Introduction The fossa of Rosenmüller, also known as the lateral pharyngeal recess, is a well-established site of origin of nasopharyngeal carcinoma. It is located in the lateral pharyngeal wall behind the cartilaginous portion of the Eustachian tube, the torus tubarius, and is named after Johann Christian Rosenmüller (JCR).Objective We present a history on the life and extensive works of Johann Christian Rosenmüller, a German physician and anatomist.Results Johann Christian Rosenmüller was a dedicated anatomist. In addition to identifying the fossa of Rosenmüller, his influence extends to various other anatomic subjects, including the Rosenmüller gland, the palpebral portion of the lacrimal gland, and the organ of Rosenmüller (i.e., the caudal remnant of the mesonephric duct). He was also an avid speleologist, studying the composition of caves and their life forms. For his contributions to this field, he had a cave in Germany and an extinct species named after him—Rosenmüllerhöhle and Ursus spelaeus Rosenmüller, respectively.Conclusion The fossa of Rosenmüller plays an important role in the growth and surgical treatment of nasopharyngeal carcinoma. We present a brief glimpse into the life of Johann Christian Rosenmüller, for whom it was named.
Keywords: fossa of rosenmüller; johann christian rosenmüller; nasopharyngeal carcinoma; history